Gamma-glutamyl transferase activity in fetal serum, maternal serum, and amniotic fluid during gestation. Issue 6 (June 1984) - Moniz, C; Nicolaides, K H; Keys, D; Rodeck, C H
Abstract : Gamma-glutamyl transferase activity was measured in fetal serum, maternal serum, and amniotic fluid in 173 pregnancies from 15 to 40 weeks' gestation. Fetal serum was obtained in the second trimester by fetoscopy and in the third trimester by umbilical cord puncture at caesarian section or vaginal delivery. Enzyme activities in maternal blood (10 IU/1, SD 2) and fetal blood (88 IU/1, SD 20) remained relatively constant throughout gestation, whereas in the amniotic fluid there was a significant decrease at term from the value in the second trimester (p less than 0.001). Electrophoretic separation of the enzyme showed one isoenzyme in the fetal blood and at least two in the amniotic fluid. The fetal isoenzyme had the same mobility as the major isoenzyme in the amniotic fluid.